Sosialisasi Pelaksanaan Pemungutan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) - Irmawati Alimuddin; Winda Ayu Virginia (Abdimas Universal, 2023)
Kaongke-ongkea Village is one of the sub-districts in Pasarwajo sub-district, Buton Regency. The people of Kaongke-ongkea Village are known to be very strong in working together to develop the region. However, in this process, there are still shortcomings in Kaongke-ongkea Village, so support from other parties is needed to realize the vision and mission of Buton Regency in terms of teaching. For this reason, Baubau Polytechnic, through the Economics and Business Department, Tax Accounting Study Program, is trying to become a medium to contribute to Kaongke-ongkea Village in overcoming the problem of increasing awareness of Land and Building Tax in Rural and Urban Communities. Kaongke-ongkea village generally earns its living as a farmer and coffee producer. The method of this activity is carried out using the lecture, discussion, and question and answer method. The lecture method is used to present the material, followed by discussion and questions and answers. Through this socialization activity, it is hoped that it can foster a spirit of compliance with tax obligations for the people in Kaongke-ongkea Village through educational material about sanctions and rates for Rural and Urban Land and Building Tax (PBB-P2) in the form of audio visuals, empowering the potential of the people of Kaongke-ongkea Village, District. Pasarwajo Buton Regency in increasing Taxpayer Awareness to pay their taxes.